Introduction to practical biochemistry - Plummer, David T (New Delhi : Mc Graw Hill India, 1987)
This is a major revision of the manual for the laboratory component of introductory biochemistry courses for undergraduates. New experiments cover molecular biochemistry and immunological methods, both major growth areas in the field. Each chapter is introduced by a section on the techniques used and the basic chemistry of the materials. Also, preceding each experiment is a brief summary of the principles involved.
Appendix 319-324p.; Index 325-332p.; Reprint 2012.
Keywords: Cell fractionation; Spectrophotometry; Chromatography